The Phenomenon of Talak to A Deceased Wife in Nagari Silantai, Sumpur Kudus District, Sijunjung District, West Sumatra Province - Paryodi Marhija Putra; Yurisman; Maulid Hariri Gani (Kirana Publisher (KNPub), 2024)
Thesis entitled